1997
DOI: 10.1136/hrt.78.6.564
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is associated with a lower exercise capacity in male chronic heart failure patients

Abstract: Objective-To study the influence of atrial fibrillation on peak oxygen uptake (peak ṼO 2 ) in chronic heart failure. An unfavourable eVect of atrial fibrillation has been shown in several patient populations, but the results have not been consistent in chronic heart failure. Methods-Data were analysed from male heart transplant candidates who were able to perform graded bicycle ergometry until exhaustion with respiratory gas analysis and measurement of heart rate. Patients in atrial fibrillation (n = 18) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 30 publications
7
65
1
3
Order By: Relevance
“…AF interferes with endothelial function (10,27) and exercise capacity (9,18,19,24), and a pathophysiological link seems to exist between the two variables (10). Our results have provided evidence that sinus rhythm conversion restores endothelial function in patients with lone AF and is partially effective (hypertension) or ineffective (diabetes) in those with comorbidities that cause endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…AF interferes with endothelial function (10,27) and exercise capacity (9,18,19,24), and a pathophysiological link seems to exist between the two variables (10). Our results have provided evidence that sinus rhythm conversion restores endothelial function in patients with lone AF and is partially effective (hypertension) or ineffective (diabetes) in those with comorbidities that cause endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…AF is associated with significant morbidity and mortality [2]. There is a 5-fold increase in the risk of stroke [3], a decline in quality of life [4][5][6] and functional status [7][8][9][10]. The rate of AF-related hospitalizations is projected to rise 2-3 fold in the coming years [11].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, patients with chronic heart failure and atrial fibrillation in whom LA diastolic function is seriously impaired, have lower exercise capacity than those with sinus rhythm. 29 In the present study, neither LV functional parameters nor transmitral flow parameters, shown in Table 1, correlated with the hemodynamic parameters during pacing-tachycardia, although IRT, one of the LV diastolic functional parameters, roughly correlated with exercise capacity. On the other hand, PVS1, but not PVS2, PVD or PVA, correlated with the degree of elevation in pulmonary circulatory pressure during pacingtachycardia (Table 2).…”
Section: La Diastolic Function and Pulmonary Circulatory Pressure Durmentioning
confidence: 41%